A Study of Unity and Coherence in Indonesian Secondary School Students’ Writing (RETAIN, 2023)
This research is aimed to investigate secondary school students’ performance in using unity and coherence in paragraph writing as well as to explore writing issues they might face during writing process. The data for analysis were writing samples and interview results from 10 East Java secondary school students who participated in this study. Students were given a link to Google Form where they must submit their writing about “culture” within 24 hours, then they were interviewed the next day to find out writing problems they might encounter during writing. Findings showed that the students wrote texts with good unity and coherence albeit minor mistakes they produced. As for writing issues, the students mentioned grammatical, choosing the correct and suitable vocabulary, misspelling, as well as structure and organization.